Comparative studies on different methods of summer rice crop establishment under drip irrigation in relation to water use, growth and yield - ., HEMLATA; KUMAR, JITENDRA; SONIT, ANAMIKA; SINHA, JITENDRA; TANDON, AMBIKA (Journal of Soil and Water Conservation, 2020)
Chhattisgarh is dominated by monocropping of rice in kharif season and cropping intensity varies from 130-137 per cent. Summer rice occupied sizeable area in the state and with increasing availability of water; area of summer rice is increasing gradually. Flood irrigation is only method of irrigation to summer rice. This causes huge losses of water from rice field due to seepage and percolation and surface evaporation at one end and unproductive loss of groundwater or surface water on the other end. In Chhattisgarh, farmers grow summer rice both in canal and tube well commands. Field to field irrigation is common practice in canal command where rice is grown. Improper irrigation methods and misconceptions are the stated reasons for the high wastage of a scare resource. Drip irrigation can potentially save a huge quantity of water in summer rice that may help in enhancement of area under summer rice crop with the existing water resources. Looking at the problems and prospects, an experiment was conducted at the Research Farm, IGKV, Raipur (C.G.) during summer seasons of 2012 and 2013. The treatments consisted of three methods of crop establishment viz. direct dry seeded rice (DSR), direct wet seeded rice (WSR) and puddled transplanted rice (TPR) as main plot treatments and four methods of irrigation Conventional irrigation, recommended practice, drip and sprinkler as sub plot treatments with rice variety MTU1010. The plant height, number of effective tillers, dry matter accumulation and seed yield and straw yield were recorded was maximum under TPR which was at par with DSR and plant stature was high in drip irrigation followed by recommended practice during both the years. The water use was the maximum in TPR followed by WSR and Conventional irrigation followed by recommended practice and minimum water use was recorded in DSR and drip irrigation system. DSRDrip irrigation and DSR-Sprinkler irrigation saved 74 and 76 percent of irrigation water respectively over WSR- conventional irrigation.